Ghosts - Gorman, Jacqueline Laks, 1955- (Milwaukee : G. Stevens Pub., 2002)
Introduces ghosts, describing what people believe about them and examples of sightings of different ghosts.
Includes bibliographical references (p. 22) and index.
Accelerated Reader AR
Keywords: Ghosts -- Juvenile literature